Academic and linguistic gains during a semester-long study abroad: A cohort case study - Cai, Wei; Li, Xiangrong; Liu, Meihua (Studies in Second Language Learning and Teaching, 2013)
The present case study investigated university students’ academic and linguistic gains during a semester-long exchange program abroad. Thirty three third-year English majors from a Chinese university answered a battery of questionnaires and 13 of them participated in semi-structured interviews both prior to and after the program. Analyses of the data showed that the participants gained greatly from the exchange program both academically and linguistically. Based on the findings, some implications about exchange programs are discussed.